Short‐chain fatty acids and microbiota metabolites attenuate ghrelin receptor signaling. Issue 12 (9th October 2019) - Torres‐Fuentes, Cristina; Golubeva, Anna V.; Zhdanov, Alexander V.; Wallace, Shauna; Arboleya, Silvia; Papkovsky, Dimitri B.; Aidy, Sahar El; Ross, Paul; Roy, Bernard L.; Stanton, Catherine; Dinan, Timothy G.; Cryan, John F.; et al.
Abstract : The gastrointestinal microbiota is emerging as a unique and inexhaustible source for metabolites with potential to modulate G‐protein coupled receptors (GPCRs). The ghrelin receptor [growth hormone secretagogue receptor (GHSR)‐1a] is a GPCR expressed throughout both the gut and the brain and plays a crucial role in maintaining energy balance, metabolism, and the central modulation of food intake, motivation, reward, and mood. To date, few studies have investigated the potential of the gastrointestinal microbiota and its metabolites to modulate GPCR signaling. Here we investigate the ability of short‐chain fatty acids (SCFAs), lactate, and different bacterial strains, including Bifidobacterium and Lactobacillus genera, to modulate GHSR‐1a signaling. We identify, for what is to our knowledge the first time, a potent effect of microbiota‐derived metabolites on GHSR‐1a signaling with potential significant consequences for host metabolism and physiology. We show that SCFAs, lactate, and bacterial supernatants are able to attenuate ghrelin‐mediated signaling through the GHSR‐1a. We suggest a novel route of communication between the gut microbiota and the host via modulation of GHSR‐1a receptor signaling. Together, this highlights the emerging therapeutic potential in the exploration of the microbiota metabolome in the specific targeting of key GPCRs, with pleiotropic actions that span both the CNS and periphery.—Torres‐Fuentes, C., Golubeva, A. V., Zhdanov, A. V., Wallace, S., Arboleya, S., Papkovsky, D. B., El Aidy, S., Ross, P., Roy, B. L., Stanton, C., Dinan, T. G., Cryan, J. F., Schellekens, H. Short‐chain fatty acids and microbiota metabolites attenuate ghrelin receptor signaling. FASEB J. 33, 13546‐13559 (2019). www.fasebj.org